Regional Disparities in the Training Market: Opportunities for Adolescents to Obtain a Company-Based Training Place Depending on Regional Training Market Conditions - Christian Michaelis; Robin Busse (International Journal for Research in Vocational Education and Training, 2021)
Context: Due to limited geographical mobility, opportunities for adolescents interested in company-based training are primarily dependent on regional training offers. Competition for company-based training among adolescents varies regionally, and thus, the chance to obtain a training contract varies as well. In this article, we investigate the opportunities for adolescents to obtain company-based training depending on regional training market conditions. We assume that the advantages of obtaining a company-based training place exist in areas of decreased competition among interested adolescents. However, the question is whether those advantages will differ between adolescents depending on characteristics such as school achievement, socioeconomic status or migration background. Furthermore, we assume that, above all, market-induced ease-of-access to company-based training exists for occupations that face hiring challenges and indicates less occupational attractiveness.